Study on the issues with field force for distribution excellence: route to market (RTM) review project 2016, British American Tobacco Bangladesh - Jebin, Tasnia (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.